The impact of an exercise intervention using low-cost equipment on functional fitness in the community-dwelling older adults: A pilot study - Rodrigues, Filipe; Amaro, Nuno; Matos, Rui; Mendes, Diogo; Monteiro, Diogo; Morouço, Pedro (Frontiers in Physiology, 2022)
Exercise interventions have shown significant improvements in the older adult population regarding functional and cognitive capacity. However, much research has applied exercise protocols that are expensive both for research and participation. Thus, high investments that are made are currently not ecologically efficient. The aim of the study was to determine whether the impact of a 20-week multicomponent exercise intervention using low-cost material could improve physical fitness in community-dwelling older adults. We tested the feasibility of this three times per week exercise protocol using an inclusive approach. Eligibility criteria included age ≥ 65 years, the ability to stand and walk with or without assistive devices, being physically inactive; medical clearance, and living in the community. Outcomes were muscle resistance measured using the chair-stand test for lower limbs, cardiorespiratory capacity measured using the 6-minute walk test, and agility and balance using the Timed-up and Go test. Flexibility was measured using the chair sit and reach for lower limbs and the back scratch for upper limbs using the dominant leg and arm, respectively. Hand grip strength was measured using a dynamometer. Thirty participants (n = 30) were recruited and included in the intention-to-treat analysis. The mean age of participants was 70 years (± 3.62 years), 100% were Caucasians, and 50% were female. There was a significant trend toward a clinically important improvement in the chair-stand (t = -5.23; p <.001; d = .36), arm curl (t = -5.21; p <.001; d = .74), 6-minute walk test (t = -4.69; p = <.001; d = .77), timed-up and go test (t = 8.788; p <.001; d = 1.18), hand grip strength (t = 2.846; p = .009; d = .23), back scratch (t = 2.243; p = .035; d = .29), and chair sit and reach (t = -3.380; p <.001; d = .15). This pilot study has provided preliminary evidence that a 20-week community-based low-cost exercise program may be effective in improving overall functional fitness in older people. The pilot trial has provided the necessary data to design future randomized-controlled trials that can be implemented in the community in an ecological feasible manner.